Testing motor skills, general and special coordinative, in young soccer - Raiola, G.; Altavilla, G. (Journal of Human Sport & Exercise, 2020)
There is need of improvement the quality of the play and the performances continually, above all the motor skills. The tests that have been made to the male young athletes, are easy to administer and are intended to investigate two different motor skills (general coordinative and specific coordinative). The purpose of this study is to monitor and to evaluate the improvement of the performance on a sample of fifteen male young soccer players of 12-13 years old. Method is experimental and has to carry out the usual parameters for monitoring the trainings. Data were collected during eight weeks. All data detected were expressed as average ± SD on: height (162.8 ± 3.45), Weight (54.6 ± 3.21), body mass index (20.6 ± 1.72) and using some field tests (Harre test, Precision shooting test and Control test of ball). Analysis of statistical data has been conducted with Test-t to check the differences between pre-test and post-test (at the beginning and at the end of a month of specific training). The significant differences have been fixed in p < .05. The results show that there is a significant difference between the performance pre and post training, in the three tests conducted. This study analyse and evaluate the reduction or the improvement of the performance, allowing at the coaches of monitor the training process.